Current practice of antithrombotic prophylaxis in pediatric kidney transplantation—Results of an international survey on behalf of the European Society for Paediatric Nephrology. (18th August 2020) - Buder, Kathrin; Zirngibl, Matthias; Bapistella, Sascha; Nadalin, Silvio; Tönshoff, Burkhard; Weitz, Marcus; ,
Abstract: Background: Renal graft thrombosis (RGT) is one of the main causes for early graft loss in pediatric kidney transplantation (KTx). Despite the lack of evidence‐based recommendations, antithrombotic prophylaxis (aP) is used to prevent RGT. Methods: An online survey supported by the European Society for Pediatric Nephrology was developed to investigate the current practice of aP in pediatric KTx recipients <18 years. Results: A total of 80 pediatric KTx centers from 37 countries participated in the survey. Antithrombotic prophylaxis was performed in 96% of the pediatric renal transplant centers (all/selected patients: 54%/42%). The main overall used drugs were as follows: low‐molecular‐weight heparin (89%), unfractionated heparin (UFH) (69%), and acetylsalicylic acid (ASS) (55%). Ten different aP management strategies were identified as follows: 51% used a single drug and 48% combined two drugs sequentially. The corresponding centers started aP predominantly within 24 hours after pediatric KTx; 51% preferred UFH for starting aP. In centers switching to a second drug (51%), this change was performed after 10 ± 6 days; of these 57% preferred ASS for maintenance aP. Reported median aP duration was 51 days (range 1‐360). Conclusions: Despite the use of aP in almost all responding pediatric KTx centers, there is no uniform management strategy. Notwithstanding, UFH seems to be the preferred drug for the early post‐operative period of pediatric KTx, and ASS for maintenance prophylaxis following pediatric KTx. Prospective studies are needed to further evaluate the benefits and risks of aP, preferably resulting in guidelines for the management in pediatric KTx.